Literature as Social Commentary: Depicting Marginalized Groups in Modern Indian English Fiction - Deepalakshmi, P. (Journal of Neonatal Surgery, 2024)
Contemporary Indian English writing has emerged as a powerful medium for social critique, foregrounding the voices and experiences of marginalized communities long excluded from dominant cultural narratives. Writers engage with issues of caste, class, gender, ethnicity, religion, disability, and sexuality to expose structural inequalities embedded within Indian society. This article examines how contemporary Indian English literature represents marginalized communities and functions as a form of social critique. Through the works of writers such as Arundhati Roy, Bama, Rohinton Mistry, Meena Kandasamy, Mahasweta Devi (in translation), and Amitav Ghosh, the study explores how literature interrogates power structures, challenges hegemonic discourses, and asserts subaltern identities. The article argues that contemporary Indian English writing not only reflects social realities but actively participates in the politics of resistance and transformation.